PENYULUHAN DAN PRAKTIKPHBS(PERILAKU HIDUPBERSIHSEHAT)DALAMMEWUJUDKANMASYARAKAT DESA PEDULI SEHAT - Yuli Andriansyah (Asian Journal of Innovation and Entrepreneurship, 2013)
The patternof clean and healthy life (PHBS) is a step that must be done to achievethe degree of optimal health for everyone. Healthy condition does not necessarilyhappen, but it should always be sought from unhealthy be a healthy lifestyle and creatinga healthy environment. These efforts should start from implanting healthy mindset to thepublic that should be initiated and cultivated by themselves. This effort is to realize thedegree of public health as high as an investment for the development of humanresources productive. Meanwhile, community health awareness and healthy clean fendpatterns, especially rural communities still very rendah.Untuk that the extension servicesrelated to clean healthy lifestyle is expected to be efforts to raise public awarenessabout the importance of efforts to clean healthy lifestyle in everyday life as well asproviding knowledge of how to make it happen so that it can realize a community thatcares healthy